THE TEACHING OF WRITING USING CONTENT AND LANGUAGE INTEGRATED LEARNING - Jihad, Adriani (STKIP Pembangunan Indonesia Makassar, 2016)
This research aims: to (1) to find out whether or not Content and Language Integrated Learning (CLIL) can improve the students’ writing ability and (2) to find out the students' motivation to learn writing by using CLIL. This research employed quasi experimental design. The population of this research was the fourth year students of STKIP YPUP of Makassar in academic year 2015/2016. This research used cluster random sampling. The sample of this research consisted of 72 students that belonged to two groups; 36 students in experimental group and 36 students in control group. The research data were collected by using writing test in which the data was analyzed by descriptive and inferential statistic through SPSS version 20.00 for windows program.The students’ result of posttest of experimental group is more significantly improved than the students’ result of posttest of control group by the mean score 80.94 > 55.69. The difference of both scores is statistically significant based on the t-test value at significant level 0.05 in which the probability value is lower than the significant level (0.00 < 0.05). The mean score of the motivation is 42.89 and it is categorized as very high motivation. It can be concluded that the use of Content and Language Integrated Learning (CLIL) improves the students’ writing skill, and the students have a high motivation in learning English writing through the Content and Language Integrated Learning (CLIL).